Market segmentation impact on industrial transformation: Evidence for environmental protection in China. (15th May 2021) - Lai, Aolin; Yang, Zhihui; Cui, Lianbiao
Abstract: This study breaks through the limitation of traditional analysis that only considers the economic development factors and further explains the reasons for the existence of inter-provincial market segmentation in China from the perspective of industrial transformation performance by combining environmental protection. The study examines panel data from 30 provinces in China from 2004 to 2017. It uses a super-efficiency slacks-based measure model to evaluate the performance of industrial transformation considering environmental protection and a fixed-effect model to analyze the impact of market segmentation on industrial transformation performance. The results show that market segmentation has an inverted "U" effect on the region's immediate and future industrial transformation performance. That is, for most regions, market segmentation can significantly improve the performance of industrial transformation. For regions with higher environmental regulations, market segmentation is more conducive to the improvement of industrial transformation performance, which shows that local governments will give up some market efficiency while carrying out environmental protection. The research results not only confirm the relationship between market segmentation and industrial transformation performance but also have important promotional significance for China's economic green development. Highlights: The Super-SBM method was used to evaluate industrial transformation performance. Market segmentation has an inverted "U" effect on industrial transformation. Local governments enacting environmental protection may sacrifice market efficiency. The losses from reduced market efficiency outweigh the gains from local protection. Coordination by the central government is critical to eliminate local protection.